Alunan / Nabhan Aminulhakeem Aminurraasyid, Nur Najla Nasuha Zalmi and Farid Al Hakeem Yuserrie - Aminurraasyid, Nabhan Aminulhakeem; Zalmi, Nur Najla Nasuha; Yuserrie, Farid Al Hakeem (2024)
This project proposes a modular, sustainable cultural hub designed to revitalize interest in Malay traditional music and dance. By incorporating interactive elements and a curvilinear form inspired by the Malay traditional dance, the design aims to create an engaging and immersive space. The project addresses a gap in cultural knowledge among younger generations by offering opportunities for learning and appreciation. Situated strategically to maximize visibility and environmental performance, the modular structure ensures adaptability and minimizes environmental impact. The design prioritizes the use of timber, aligning with the project’s cultural focus and sustainability goals. Ultimately, this cultural hub seeks to foster community engagement, preserve Malay heritage, and inspire future generations.